Modularity : understanding the development and evolution of natural complex systems - Callebaut, Werner; Rasskin-Gutman, Diego (Cambridge, Mass. : MIT Press, 2005)
Experts from diverse fields, including artificial life, cognitive science, economics, developmental and evolutionary biology, and the arts, discuss modularity. Modularity--the attempt to understand systems as integrations of partially independent and interacting units--is today a dominant theme in the life sciences, cognitive science, and computer science. The concept goes back at least implicitly to the Scientific (or Copernican) Revolution, and can be found behind later theories of phrenology, physiology, and genetics; moreover, art, engineering, and mathematics rely on modular design principles. This collection broadens the scientific discussion of modularity by bringing together experts from a variety of disciplines, including artificial life, cognitive science, economics, evolutionary computation, developmental and evolutionary biology, linguistics, mathematics, morphology, paleontology, physics, theoretical chemistry, philosophy, and the arts. The contributors debate and compare the uses of modularity, discussing the different disciplinary contexts of "modular thinking" in general (including hierarchical organization, near-decomposability, quasi-independence, and recursion) or of more specialized concepts (including character complex, gene family, encapsulation, and mosaic evolution); what modules are, why and how they develop and evolve, and the implication for the research agenda in the disciplines involved; and how to bring about useful cross-disciplinary knowledge transfer on the topic. The book includes a foreword by the late Herbert A. Simon addressing the role of near-decomposability in understanding complex systems
Foreword / Herbert A. Simon -- I. Introduction -- The Ubiquity of Modularity / Werner Callebaut --II. Evo-Devo : The Making of a Modular World -- Natural Selection and the Origin of Modules / Günter P. Wagner, Jason Mezey, and Raffaele Calabretta -- Evolutionary Modules : Conceptual Analyses and Empirical Hypotheses / Robert N. Brandon -- Evolutionary Developmental Biology Meets Levels of Selection : Modular Integration or Competition, or Both? / Rasmus G. Winther -- Modularity in Evolution : Some Low-Level Questions / Lee Altenberg -- Evolutionary Lock-In and the Origin of Modularity in RNA Structure / Lauren Ancel Meyers and Walter Fontana -- Amphibian Variations : The Role of Modules in Mosaic Evolution / Gerhard Schlosser -- III. Evo-Patterns : Working Toward a Grammar of Forms -- The Remodularization of the Organism / Daniel W. McShea and Carl Anderson -- Modularity : Jumping Forms within Morphospace / Diego Rasskin-Gutman -- Morphological Modularity and Macroevolution : Conceptual and Empirical Aspects / Gunther J. Eble -- Hierarchical Integration of Modular Structures in the Evolution of Animal Skeletons / Roger D.K. Thomas -- Modularity in Art / Slavik V. Jablan -- Modularity at the Boundary Between Art and Science / Angela D. Buscalioni [and others] -- IV. Modularity of Mind And Culture -- Evolutionary Connectionism and Mind/Brain Modularity / Raffaele Calabretta and Domenico Parisi -- Modularity and Chunking / Fernand Gobet -- Modularity of Cognitive Organization : Why It Is so Appealing and Why It Is Wrong / Boris M. Velichkovsky -- Decomposability and Modularity of Economic Interactions / Luigi Marengo, Corrado Pasquali, and Marco Valente -- The Natural Logic of Communicative Possibilities : Modularity and Presupposition / D. Kimbrough Oller.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Evolution (Biology); Natural selection; Chaotic behavior in systems; Modularity (Psychology); Chaos; Modularité (Psychologie); SCIENCE -- Life Sciences -- Evolution; Chaotic behavior in systems; Evolution (Biology); Modularity (Psychology); Natural selection; BIOMEDICAL SCIENCES/Evolution; BIOMEDICAL SCIENCES/General; book